COMPARISON OF PAIN AFTER SURGERY IN THYROID LOBECTOMY WITH VERSUS WITHOUT DRAIN - ALI SHAYYAN , GHAZANFAR ZULFIQAR , ALI SALMAN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Objective: To compare the average pain scores using the Visual Analog Scale (VAS) in patients who had a thyroid lobectomy either with or without a surgical drain. Study Design: Prospective randomised controlled trial. Place and Duration of Study: ENT and General Surgery departments, Shaikh Zayed Hospital, Lahore, from June 2025 to September 2025. Methodology: Sixty patients scheduled for thyroid lobectomy for small, benign thyroid nodules(<4 cm) were chosen. They were divided into Group A (drain used, n=30) and Group B (no drain used, n=30). The main goal was to check pain scores at 24 and 48 hours after the operation. We also used ultrasound to check for fluid in the neck on the first day. Results: Both groups were very similar in age and health before surgery (p>0.05). Group B had much less pain on Day 1 (2.8 ± 0.9) and Day 2 (1.4 ± 0.7) compared to Group A (5.9 ± 1.2 and 3.8 ± 1.0; p<0.001). Ultrasound showed no real difference in fluid build-up between the two groups (p=0.450). No patients had serious heamatoma or large swellings. Conclusion: Skipping the drain in simple thyroid lobectomy cases is safe and helps patients feel much more comfortable without increasing the risk of complications.